Maternal and perinatal outcome of covid-19 in obstetric cases: 9 months experience from east java tert iary referral hospital - Wardhana M.P, -
Abstract Background: Covid-19 infection in vulnerable obstetric patients still requires a lot of research, especially in developing countries to help determine the best policy to manage it. Objective: To analyze the characteristic of Covid-19 infection in obstetric patients. Methods: In an East Java tertiary Covid-19 referral hospital, a case control analysis was conducted using medical records on obstetric cases of Covid-19 infection from March until November 2021. Results: Covid-19 was identified in 109 cases (9.3%) from 1170 patients who came to our obstetric room. Majority came in pregnancy state with 76% and had delivered 93.6%. Most patients were asymptomatic (68.8%) with minimal contact history (2.8%). Comorbidity found in 41.3% cases, obesity and hypertension in pregnancy dominated the cases. Symptomatic cases were associated with lower gestational age (p=0,005) and birthweight (p=0,015), low lymphocyte count (p=0,006), abnormal chest X-Ray (p<0,001), intensive care admission (p=0,002) and maternal death (p<0,001), while asymptomatic cases were associated with more reactive antibody test (p=0,002). Conclusion: There were a high number of Covid-19 obstetric cases with the majority asymptomatic and came for delivery. Significantly higher reactive antibody tests in asymptomatic cases may aid Covid-19 identification. Covid-19 symptoms should be given more consideration, because they are linked to a lower gestational age, birth weight, poor clinical parameters, the need for intensive care, and maternal mortality.